Contingencia estructural en el nivel de ingresos: un análisis en medianas y grandes empresas orenses. - Batallas Astudillo, Ingrid Lisseth; Luna Luna, Arelys Johanna (My University, 2021)
Currently, the business sector requires the systematized implementation of internal organizational structures that allow medium and large companies to expand economically. The purpose of this research is to analyze the impact of human capital management, managerial and administrative strategies, and efficient use of resources as part of the structural contingency of large and medium-sized companies in the province of El Oro. The research is based on a quantitative approach of correlational scope with cross-sectional design, the statistical software Stata 14 was used to manipulate 120 observations of the Enterprise Structural Survey (ENESEM) of the National Institute of Statistics and Census (INEC) corresponding to the province of El Oro, the variation of the level of income of the companies was measured through an econometric model of linear multiple regression and statistical tests of collinearity, normality and homoscedasticity in the residuals. Regarding the results, the level of income of the organizations in the business sector depends significantly on the human capital focused on top management; administrative, financial and computer technicians; and the amount and efficient use in the consumption of basic services, fuel, supplies, materials and tools. In fact, the organizational structure focused on the area of qualified personnel and the correct management of resources positively influences the economic development of medium and large companies in the region.
Actualmente, el sector empresarial requiere la implementación sistematizada de estructuras organizativas internas, que permitan a las medianas y grandes empresas expandirse económicamente. La investigación tiene como finalidad analizar el impacto de la gestión del capital humano, estrategias gerenciales y administrativas, y uso eficiente de los recursos como parte de la contingencia estructural de grandes y medianas empresas de la provincia de El Oro. La pesquisa parte de un enfoque cuantitativo de alcance correlacional con diseño transversal, se utilizó el software estadístico Stata 14 para manipular 120 observaciones de la Encuesta Estructural Empresarial (ENESEM) del Instituto Nacional de Estadística y Censos (INEC) correspondiente a la provincia de El Oro, se midió la variación del nivel de ingresos de las empresas mediante un modelo econométrico de regresión múltiple lineal y pruebas estadísticas de colinealidad, normalidad y homocedasticidad en los residuos. Referente a los resultados, el nivel de ingresos de las organizaciones del sector empresarial depende significativamente del capital humano focalizado en la alta dirección; técnicos administrativos, financieros e informáticos; y del importe y uso eficiente en el consumo de servicios básicos, combustible, suministros, materiales y herramientas. En efecto, la estructura organizativa enfocada en el área de personal calificado y en el correcto manejo de los recursos influye positivamente en el desarrollo económico de medianas y grandes empresas orenses.
Keywords: ENFOQUE CONTINGENTE; NIVEL DE INGRESOS